Bacteriological profile of diabetic foot ulcers - Sarita Otta; Nagen Kumar Debata; Bichitrananda Swain (Wolters Kluwer Medknow Publications, 2019)
Background: Foot infections are the major complications of diabetes mellitus and lead to the development of gangrene and ultimately amputation of the limb. Proper diagnosis of the causative agents and their antibiotic susceptibility play a significant role in preventing adverse prognosis of diabetic foot. Aim: The study aims to establish the bacteriological profile of diabetic foot ulcers as well as to note resistance pattern of the implicated organisms. Materials and Methods: One hundred and forty-eight patients having diabetic foot ulcers of Wagner's Grade 1 or above were included in this study. Debrided tissue, pus, or swabs from the base of the ulcers were subjected to aerobic and anaerobic culture. The organisms were identified, and further antibiotic sensitivity of the aerobic bacteria was conducted by Kirby-Bauer's disc diffusion method. Results: Two hundred and forty aerobic and 21 anaerobic bacteria were isolated from these ulcers; Staphylococcus aureus and Bacteroides spp. are the most common aerobic and anaerobic bacteria isolated, respectively. Of the S. aureus, 77.8% were methicillin resistant, while 42.1% of the Gram-negative Enterobacteriaceae were extended-spectrum beta-lactamase (ESBL) positive. Klebsiella spp. was the highest ESBL producer whereas Acinetobacter spp. was the highest metallo-beta-lactamase producer. Linezolid, teicoplanin, and vancomycin were the most sensitive drugs for Staphylococcus spp. Gram-negative isolates were mostly sensitive to cefoperazone-sulbactam and imipenem. Pseudomonas spp. was mostly sensitive to imipenem and piperacillin-tazobactam, whereas Acinetobacter spp. was sensitive to netilmicin and levofloxacin. Conclusion: As diabetic ulcers are often infected by multidrug-resistant bacteria, a knowledge of the common bacterial pathogens implicated as well as their sensitivity pattern helps the clinician to choose the proper antibiotic for a timely treatment.